. Metode Gyssens Sebagai Pilihan Utama Dalam Evaluasi Kualitatif Penggunaan Antibiotik di Indonesia - Dheti Efrilia -; Novita carolia; syazili mustofa; rasmi zakiah oktarlina (Medula, 2023)
Antibiotic resistance is a global health problem in the world. Antibiotic resistance is defined as the absence of inhibition of bacterial growth by systemic administration of antibiotics with normal doses or minimal inhibitory levels. The World Health Organization (WHO) seeks to control antibiotic resistance globally by making global action plans to combat bacterial resistance to antibiotics, namely increasing the wise use of antibiotics and evaluating the use of antibiotics. The qualitative evaluation that can be used is the Gyssens method. The Gyssens method was chosen because this method has more specific aspects to evaluate each of the important parameters included in the use of antibiotics such as indication, effectiveness, safety, price and spectrum, and can also evaluate treatment duration, dose, interval, and route of administration as well as time of giving. Therefore, this method is the main choice for evaluation of antibiotics in Indonesia.